2019
DOI: 10.1504/ijtm.2019.099606
|View full text |Cite
|
Sign up to set email alerts
|

Crafting better team climate: the benefits of using creative methods during team initiation

Abstract: This study employs a mixed methods approach to investigate the effect of creative methods, the combinative use of model building and storytelling, during team initiation on team climate, a critical people-related factor in the management of collective innovation work. Qualitative analysis provides empirical evidence that creative methods benefit team initiation by raising participative confidence, engagement with the social environment as well as the team activities, friendly competition among team members, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Since the instrument can also be used as a full-scale measurement of team climate, this study used TCI as merely a one-dimensional scale. According to previous studies, the full-scale was reported to have a Cronbach's alpha of 0.91 for the Bahasa Indonesia version (Antonio et al, 2021) and 0.95 for the English version (Primus and Jiang, 2019), which indicated a high reliability. This instrument has a 5-point response scale from "strongly disagree" to "strongly agree", in which higher scores suggest a more desirable team climate.…”
Section: Methodsmentioning
confidence: 94%
“…Since the instrument can also be used as a full-scale measurement of team climate, this study used TCI as merely a one-dimensional scale. According to previous studies, the full-scale was reported to have a Cronbach's alpha of 0.91 for the Bahasa Indonesia version (Antonio et al, 2021) and 0.95 for the English version (Primus and Jiang, 2019), which indicated a high reliability. This instrument has a 5-point response scale from "strongly disagree" to "strongly agree", in which higher scores suggest a more desirable team climate.…”
Section: Methodsmentioning
confidence: 94%
“…Therefore, boundary-spanning activities have become an essential issue for scholars from the innovation perspective. However, the existing literature mainly focuses on how to improve team innovation performance through factors within the team, such as leadership style [2,3], team composition [4,5], the characteristics of team members [6][7][8], team atmosphere [9][10][11] and team human resource management [12]. Research on the influence of collaborative innovation boundary-spanning activities on Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Does Team Boundary-spanning Activities On Innovation Perform...mentioning
confidence: 99%
“…Furthermore, LSP stimulates commitment to the team, resulting in active participation in the decision-making. According to Primus & Jiang (2019), LSP facilitates developing novel and surprising solutions to problems. Zenk et al, 2021 conclude that LSP improves the creative team output.…”
Section: Lego Serious Playmentioning
confidence: 99%